Hematological Parameters as Prognostic Biomarkers in Patients with Cardiovascular Diseases - Monteiro Júnior, José Gildo de Moura; de Oliveira Cipriano Torres, Dilênia; Filho, Dário C. S. (Current Cardiology Reviews, 2019)
Cardiovascular diseases are the major causes of preventable health loss from disease in the world and lead to functional disturbances including hematological parameters. The inflammatory and hypoxemic nature of cardiovascular diseases causes a stimulus in the bone marrow and, depending on the intensity of this stimulus, there is a release of immature cells or increase of other cells in the bloodstream. Therefore, their presence in the circulation is an important variable used to diagnose, stratify and predict diseases. In the last five decades, with the advent of automated counting of immature cells in the peripheral blood, the hemogram was transformed into a clinical tool of great importance in hospital surveillance for demonstrating this daily variability in the hematopoietic response according to the existing injury in the patient. Studies have shown that the presence of nucleated red blood cells and increases in mean platelet volume, immature granulocytes and neutrophil to lymphocyte ratio in the systemic circulation are independent prognostic biomarkers. This review article has as main objective to demonstrate the association of these hematological parameters to cardiovascular diseases, emphasizing their importance in clinical decision making.
Keywords: biomarkers